Esophagic anastomosis.: Early postoperatory study - Aliano, Franklin; Lyonnet, Alberto; Parodi, Hernán (Cirugía del Uruguay, 1980)
The disruption of the esophagic anastomoses are very important and their diagnostic is difficult. We propase a method of radiologic study for their early diagnostic and we presente our first résults.